2021
DOI: 10.2106/jbjs.rvw.21.00008
|View full text |Cite
|
Sign up to set email alerts
|

Revision Arthroplasty Versus Open Reduction and Internal Fixation of Vancouver Type-B2 and B3 Periprosthetic Femoral Fractures

Abstract: Revision arthroplasty (RA) continues to be considered the gold standard in the surgical treatment of Vancouver type-B2 and B3 periprosthetic femoral fractures. However, open reduction and internal fixation (ORIF) has been associated with satisfactory outcomes. Thus, there is an ongoing discussion regarding the optimal surgical strategy for the treatment of these fractures.In this systematic review and meta-analysis, no significant differences in clinical and radiographic outcome were observed between ORIF and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Haider et al also found revision figures of 22.9% versus 13.5%, with ORIF versus revision arthroplasty, respectively, a difference that was only found in B3 and not in B2 fracture types. 43,55…”
Section: Periprosthetic Fractures In the Vancouver Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Haider et al also found revision figures of 22.9% versus 13.5%, with ORIF versus revision arthroplasty, respectively, a difference that was only found in B3 and not in B2 fracture types. 43,55…”
Section: Periprosthetic Fractures In the Vancouver Classificationmentioning
confidence: 99%
“…The latter group had lower rates of reoperation, lower rates of loosening of the femoral component, and better results in the Parker Mobility Score. 55…”
Section: Periprosthetic Fractures In the Vancouver Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence in the trauma literature that fixation of these types of fractures may offer similar outcomes to revision arthroplasty, particularly in older patients with decreased functional demand [9]. More recently, studies have found similar outcomes when managing B2 and B3 fractures with open reduction and internal fixation (ORIF) when compared to RA [9][10][11]. At our institution periprosthetic fractures, including all Vancouver B variants, are primarily treated with fixation and only revised if the stability of the original stem cannot be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a debate on the need to follow these recommendations in all patients. Various authors have argued that, in certain circumstances, VB2 PPHF could be successfully treated using the ORIF technique (3,8,9,10). For this reason, in some studies, ORIF has been compared to revision arthroplasty (RA) for this type of fracture, and equivalent if not better results have been obtained (8,11,12,13,14,15,16,17).…”
Section: Introductionmentioning
confidence: 99%